Three new species of Habenaria (Orchidaceae) from Serra da Canastra, Minas Gerais, Brazil - Batista, J. A. N.; Carvalho, B. M.; Ramalho, A. J.; Bianchetti, L. B. (Phytotaxa, 2010)
As part of a floristic survey of the genus Habenaria in Serra da Canastra, Minas Gerais, Brazil, three new species of Habenaria (Orchidaceae, Orchideae), H. psammophila, H. pseudoculicina and H. canastrensis, are described and illustrated. Habenaria psammophila also occurs in the state of Goias and the Federal District, in the central plateau, whereas H. canastrensis and H. pseudoculicina are known only locally. These are the first records of endemic taxa of Orchidaceae from Serra da Canastra and further highlight the rich endemic flora of this region.